Fast-Growing Company Outfit7: Growth Supported by Efficient Culture and Talent Management (Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024, 2024)
Outfit7, globally renowned for its ˈTalking Tom & Friendsˈ franchise, encountered significant challenges during its rapid growth. The key challenges included effective talent management, maintaining a strong organisational culture, and adapting to international investments. The company successfully implemented comprehensive strategies for attracting, developing, and retaining top talent, which allowed it to create an innovative and motivating work environment. Simultaneously, Outfit7 maintained a culture focused on creativity, collaboration, and open communication, which was critical for adapting to global markets and maintaining a competitive edge. By leveraging technology and process automation, the company enhanced efficiency, stayed aligned with its strategic goals, expanded into new markets, and improved operational performance.. The case of Outfit7 highlights the essential role of talent management and organisational culture in driving sustainable growth in a competitive global business environment.